Cultural Factors Influencing Student’s Response toward seeking Guidance and Counselling Services in Private Primary Teachers Training Colleges In Nyanza Region, - Peter, Dr. MBERA, Aiko G.; Ogonyo, MBERA Jared (IJRDO- Journal of Educational Research, 2017)
The purpose of this study was to investigate cultural factors that influence student’s low turnout to guidance and counselling services among college students in private teachers training colleges in Nyanza Province. The study used descriptive survey and employed a questionnaire (structured and semi- structured) for students in teacher training colleges as data collection instrument. The population of the study comprised the students in private teachers training colleges in the region. The population was 2000 students and had a sample of 200. The questionnaires were pre-tested by being administered to 30 respondents from two schools which were not included in the study. The scores obtained from the first and second tests were 0.76 and 0.77 respectively. The descriptive statistics including percentages mean and frequency tables were used to analyze the data. The statistical tools, which were used in the analysis of the data, were frequencies and percentages. Tabulation constituted the main form of organizing and presenting the collected information. The findings revealed that cultural factors that influence student’s low turn-out to guidance and counselling services was sixty four percent (64%).The recommendations were made that the institutional heads to be trained in Guidance and Counselling services. The study ethical considerations were carefully taken care of in the study